Cultivating Resilience in Families Who Foster: Understanding How Families Cope and Adapt Over Time. Issue 4 (3rd August 2016) - Lietz, Cynthia A.; Julien‐Chinn, Francie J.; Geiger, Jennifer M.; Hayes Piel, Megan
Abstract : Families who foster offer essential care for children and youth when their own parents are unable to provide for their safety and well‐being. Foster caregivers face many challenges including increased workload, emotional distress, and the difficulties associated with health and mental health problems that are more common in children in foster care. Despite these stressors, many families are able to sustain fostering while maintaining or enhancing functioning of their unit. This qualitative study applied an adaptational process model of family resilience that emerged in previous studies to examine narratives of persistent, long‐term, and multiple fostering experiences. Data corroborated previous research in two ways. Family resilience was again described as a transactional process of coping and adaptation that evolves over time. This process was cultivated through the activation of 10 family strengths that are important in different ways, during varied phases. Abstract : Video Abstract